Applying meta-abilities to outsourcing: An individual based conceptual framework - Selamat, Mohamad Hisyam; Choudrie, Jyoti; Grey, Susan (John Wiley & Sons, Ltd., 2009)
To cope with the current turbulent times, organisations’ are seeking a range of solutions and one of the most publicised strategies for this in recent times is outsourcing. In the Information Systems (IS) area, outsourcing has fast become an essential part of an organisation’s IS strategy. By signing outsourcing agreements, firms expect to reduce their overall Information Technology(IT) costs, focus on their core competencies, and gain superior technical resources. This paper offers a conceptual model for the area of outsourcing, which is based primarily on meta-abilities.